Internalisasi Nilai Ekoteologi Islam melalui Edukasi Pengelolaan Sampah dalam Pemberdayaan Masyarakat di Kelurahan Salomallori - Yusriani, Yusriani; Yanti, Hardi; Mursidin, Mursidin; Hamdi, Hamdi; Hasriani, Vivi; Rajabil, Abdul; Ramadhani, Nur Azizah; Jusyana, A. Erwina; Fajri, Nur; Wahyudi, Wahyudi (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
Household waste is a significant challenge in environmental management at the community level. Low public awareness of waste management demonstrates the need for an approach that is not only technical but also based on spiritual values. This Community Service (PKM) activity aims to internalize Islamic ecotheological values through waste management education and community empowerment in Salomallori Village. The method used was an educational-participatory approach through door-to-door outreach to 20 households, including reflective religious dialogue, waste sorting demonstrations, and mentoring in the practice of the 3Rs (reduce, reuse, recycle). The results of the activity indicated an increase in community understanding of ecological responsibility as part of the mandate of the caliphate. Furthermore, approximately 12 of the 20 households (60%) began implementing simple practices of separating organic and inorganic waste. These findings demonstrate that an approach based on Islamic ecotheological values is effective in building community environmental awareness. This educational model has the potential to be replicated in communities with strong religious characteristics.